Effects of conversion of rangeland to dry farming on surface runoff, soil erosion and sediment yield in Kardeh Drainage Basin, Iran - Saeidyan, Farid (2012)
Land use/cover changes may affect hydrological properties, soil erosion and sediment yield of a basin. In arid and semi-arid regions, these changes mostly appear as conversion of rangelands to dry farming. The main research question is: what is the effect of such conversion on hydrologic and soil characteristics of the basin. This research evaluates the trend of converting rangelands to dry farming in Kardeh Drainage Basin, Iran and its effects on surface runoff, soil erosion and sediment yield. Hydrologic simulations based on different design rainfall and the impacts of different scenarios of vegetation conditions on flood peak were assessed. Land use and vegetation maps 1970 and 2006 were prepared using aerial photographs and satellite images. Rainfall-Runoff relations and flood routing in the channel were obtained by using curve number and Muskingum methods respectively in HEC-HMS model. The effect of temporal distribution of rainfall on hydrologic simulation was studied. Future flood simulations were evaluated based on six future land use scenarios of vegetation cover condition ranging from highly vegetated cover (good) to sparsely vegetated condition (poor). The Erosion Potential Method (EPM) was used to evaluate the total annual sediment discharge for the basin. Multiple regression approach was use to identify the most effective factors on the sediment yield of the sub basin. The results of the study showed a drastic change of land use between 1970 and 2006 especially in the increment of dry land (91%) and reduction of rangeland (about 13%). In the same period, the predicted peak discharge at sub basin level appeared to increase more than the runoff volume. In addition, runoff concentration time and lag time was reduced as well as time to peak of hydrograph. The simulation output indicated that for a two year rainfall return period, changes of peak discharge increased significantly (70%). While for a rainfall return period of 100 years, the changes of peak discharge decreased (41%). In future land use scenarios, simulations of 1 poor range condition to good range condition, peak discharge decreases drastically; however, the effects diminished as design rainfall return period increased. Erosion and sediment yields increased about 82% from 1970 to 2006. Multiple regression analysis showed that 70% of the changes in sediment yield in the year 2006 are due to the effects of increase in dry farming area (R2= 70%, α < 0.05). The results point to the fact that converting rangelands to dry farming in an arid and semi-arid region such as the Kardeh Drainage Basin, leads to many negative effects on hydrological properties, including increase in runoff coefficient, peak discharge, runoff volume, and decrease in concentration time, lag time and time to peak. The land use change was the major contributing factor to the increase of sediment yield in the basin.